The Juridical Analysis of Default Actions Made by Mudharib in Mudharabah Financing with Mortgage Guarantees - Fikry, Muhammad Tsaqif (Jurnal Konstatering, 2022)
Any financing issued by KSPPS carries the risk of non-return of the disbursed funds or is called non-performing financing which results in default debtors. , and if the financing is jammed due to the default customer not being resolved, it will affect the business continuity of KSPPS BMT An Najah Pekalongan. Therefore, in order to avoid the risk of loss in providing financing facilities, KSPPS BMT An Najah Pekalongan in channeling financing requests the imposition of collateral from its customers, including Mudharabah financing. The approach that the author uses in this study is a Juridical Sociological approach. The Sociological Juridical Approach emphasizes research aimed at obtaining legal knowledge empirically by going directly to the object. Sociological Juridical Research is legal research using secondary data as initial data, which is then followed up with primary data in the field or on the community. The results obtained from this study are that the implementation of Mudharabah financing with mortgage guarantees at KSPPS BMT An Najah includes submission of financing applications, financing analysis, financing approval, financing agreements, disbursement of financing, and monitoring. All of these steps are carried out using the 5C principles which include Character (characteristics of prospective financing members, such as honesty, behavior and obedience), Capital, Capacity (ability), Collateral, Condition of economy. Furthermore, for the settlement of default Mudharib at KSPPS BMT An-Najah is the settlement of Mudharabah financing disputes at KSPPS BMT An Najah, including rescheduling (rescuing), reconditioning, restructuring (rearrangement).Keywords: Guarantees; Financing; Mortgage; Mudharabah.